New species, new records and notes of Afrotropical Chaetophora Kirby & Spence, 1817 (Coleoptera: Byrrhidae: Syncalptinae) - Matsumoto, Keita (Zootaxa, 2021)
Three new species of Chaetophora Kirby & Spence, 1817 (Coleoptera: Byrrhidae: Syncalptinae) are described: C. morettoi sp. nov., C. milesi sp. nov. & C. smithi sp. nov. from Côte d’Ivoire, Sierra Leone and Zambia respectively. C. medleri Johnson 1978 is redescribed with additional faunistic records. Morphological features of C. russelli (Fiori, 1978) are also discussed. A diagnostic key to currently known species of Afrotropical Chaetophora is provided.